1985
DOI: 10.3758/bf03213361
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrator influence on observer diet preference: Effects of simple exposure and the presence of a demonstrator

Abstract: Previous studies in our laboratory have demonstrated that a naive rat (an observer), after interacting briefly with a previously fed conspecific(a demonstrator), will exhibit an enhanced preference for the diet its demonstrator had been fed. The present studies were undertaken to determine whether demonstrator-induced alterations in observer diet preference were the result of simple exposure of observers to diet-identifying cues emitted by demonstrators during the period of demonstrator-observer interaction. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 9 publications
6
57
0
1
Order By: Relevance
“…Conditioned food aversion is a powerful experimental tool to modify animal diets (Galef, 1985). We have shown that it is a potential management tool to prevent livestock from grazing poisonous plants like larkspur (Ralphs, 1997), locoweed , and ponderosa pine (JA Pfister, unpublished results).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Conditioned food aversion is a powerful experimental tool to modify animal diets (Galef, 1985). We have shown that it is a potential management tool to prevent livestock from grazing poisonous plants like larkspur (Ralphs, 1997), locoweed , and ponderosa pine (JA Pfister, unpublished results).…”
Section: Resultsmentioning
confidence: 99%
“…Simple exposure to a food did not enhance preference. However, the presence of a demonstrator rat that had eaten a specific food, even if that food was consumed at another location, enhanced the observer rats' preference for that food (Galef et al 1985). Delays of up to 4 h between the demonstrator's meal and interaction with the observer did not impede the establishment of preference for the food.…”
Section: Social Facilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…The method we used to answer the first of these questions was similar to that used in the first experiment described above, except in how we exposed demonstrators to diets and in the conditions under which demonstrators and observers interacted (Galef, Kennett, & Stein, 1985;. As shown in Figure 7, when a demonstrator and its observer interacted, the demonstrator was anesthetized and held in a wire-mesh tube inserted into a cardboard bucket.…”
Section: Social Influences On the Food Choices Of Norway Ratsmentioning
confidence: 99%